2020
DOI: 10.1097/yct.0000000000000717
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy for Depression in Transgender Patients

Abstract: There is very limited information regarding the effectiveness of electroconvulsive therapy (ECT) as a treatment for major depressive disorder in transgender patients. This population is also at risk for comorbid conditions, such as posttraumatic stress disorder and substance use that could impact the outcome of ECT. We report our experience with the use of ECT in this population. Clinical and response characteristics of 7 consecutive cases are described in this series. All patients had multiple psychiatric dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…M. Diamond et al, 2012;Grannis et al, 2021;Pachankis, Williams, et al, 2020;Russon, Morrissey, et al, 2022;Saewyc et al, 2014;Turban et al, 2020;van der Miesen et al, 2020;Wang et al, 2013), including four therapeutic interventions (G. M. Diamond et al, 2012;Pachankis, Williams, et al, 2020;Russon, Morrissey, et al, 2022), and four gender-affirmative treatments (Achille et al, 2020;Grannis et al, 2021;Turban et al, 2020;van der Miesen et al, 2020). Other interventions (n = 4) provided standard treatment un-modified for SGM people (Beard et al, 2017;Mormando, et al, 2021;Plöderl et al, 2017;Zhang et al, 2020). Lastly, only three studies assessed the longer-term (3-18 months) outcome of the interventions (Achille et al, 2020;Pachankis, Williams, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Diamond et al, 2012;Grannis et al, 2021;Pachankis, Williams, et al, 2020;Russon, Morrissey, et al, 2022;Saewyc et al, 2014;Turban et al, 2020;van der Miesen et al, 2020;Wang et al, 2013), including four therapeutic interventions (G. M. Diamond et al, 2012;Pachankis, Williams, et al, 2020;Russon, Morrissey, et al, 2022), and four gender-affirmative treatments (Achille et al, 2020;Grannis et al, 2021;Turban et al, 2020;van der Miesen et al, 2020). Other interventions (n = 4) provided standard treatment un-modified for SGM people (Beard et al, 2017;Mormando, et al, 2021;Plöderl et al, 2017;Zhang et al, 2020). Lastly, only three studies assessed the longer-term (3-18 months) outcome of the interventions (Achille et al, 2020;Pachankis, Williams, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies assessed biological and medically based treatments, including one study that assessed electroconvulsive therapy, and four that examined the impact of hormonal treatments, all five focused on GM people. Mormando et al (2021) examined the effect of electroconvulsive therapy on major depressive disorder in seven trans-identifying people. Suicidal ideation was measured using a single item from the Beck depression inventory-II (Beck et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…With the very recent exception of electroconvulsive therapy (ECT), neuromodulation in TGD patients is not addressed in the literature [7][8][9][10][11]. Yet, compared to others, lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) patients are more likely to have histories of trauma, self-harm, and substance abuse [1].…”
Section: Discussionmentioning
confidence: 99%
“…Luccarelli et al [ 13 ] found a reduction in depressive symptoms as measured by the Quick Inventory of Depressive Symptomatology in 19 patients with a mix of MDD and bipolar affective disorder. Similarly, Oka et al [ 14 ] found a significant clinical improvement comparable to a control sample of non-LGBTQ patients receiving ECT, while Mormando et al [ 15 ] outlined six patients with multiple psychiatric diagnoses who were refractory to pharmacologic intervention while receiving GAHT. In keeping with the two aforementioned case series, they found ECT helped improve depressive symptomatology (using Beck Depression Inventory) and observed a reduction in suicidality.…”
Section: Literature Reviewmentioning
confidence: 99%